Interdisciplinary Approaches to Renewable Energy Adoption in Developing Economies - Muhammad Saad Raza; Hina Farooq (Global Journal of Multidisciplinary and Applied Sciences, 2025)
Renewable energy adoption in developing economies is shaped by a tight coupling of technical feasibility, affordability, institutional capability, social legitimacy, and political economy. This article argues that purely “technology-first” energy transitions underperform when grid constraints, financing frictions, behavioral barriers, and governance weaknesses are treated as secondary issues. Drawing on an interdisciplinary lens—integrating engineering, economics, public policy, behavioral science, and institutional analysis—we propose a practical framework for accelerating deployment while improving equity and system reliability. Key pathways include de-risking investment through blended finance and credible procurement, strengthening grid flexibility and planning, building community trust through inclusive participation, and aligning energy transition objectives with development priorities such as jobs, health, and energy access. The article concludes that the fastest gains come from coordinated action: policy credibility + bankable projects + grid readiness + social acceptance + capable institutions, rather than isolated reforms.